IMPLEMENTASI REST API PADA APLIKASI E-BIN PENGELOLAAN SAMPAH BERBASIS WEB DAN MOBILE - Prasetiyo, Thio; Aji, Adam Sekti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Waste is a rather serious issue. One of the main factors is the lack of awareness in society regarding proper waste management and disposal, as well as a lack of concern for environmental cleanliness, which results in an increasing accumulation of waste that can lead to environmental pollution and diseases affecting public health. Therefore, this research was conducted to provide an alternative solution for the community, enabling people to easily manage and dispose of waste properly and instill the habit of waste separation. This was achieved through the design and development of a web and mobile-based waste management application called E-Bin for the residents of Ciwaru village. The research was carried out using the waterfall method, which involved data collection and system design based on existing systems. The application was successfully built and resulted in two systems a web system for administrators and a mobile application that is easily accessible to the community. The application was developed using Android Studio with Java as the programming language, MySQL as the database server, and Visual Studio Code as a supporting tool. It has been tested using black-box testing, demonstrating that the application functions well and is suitable for use.